Aerosol filter analysis using polarized optics EDXRF with thin-film FP method. Issue 2 (17th April 2014) - Moriyama, Takao; Morikawa, Atsushi; Doi, Makoto; Fess, Scott
<x content-type="archive" xml:space="preserve">Abstract</x> Interest in atmospheric aerosol issues has been increasing worldwide. X-ray fluorescence (XRF) is an important atmospheric aerosol monitoring tool for inorganic component analysis, because XRF is a rapid and easy analysis method. In particular, Energy dispersive X-ray fluorescence (EDXRF) has drawn attention for aerosol analysis. However, EDXRF has difficulties that: (1) many overlapping peaks exist for aerosol filter analysis and (2) many thin-film standard samples are required when an empirical calibration method is employed. Accurate analysis method of aerosol filter samples without the need for large sets of standards by semi-quantitative analysis software RPF–SQX (Rigaku profile fitting–spectra quant X), which includes the exact profile fitting and thin-film fundamental parameter (FP) method, is described using the EDXRF spectrometer equipped with secondary targets and polarized optics.